Colonisation of the Future, the Time of the Émigré, the History of the Earth: Ignacy Domeyko’s Moje Podróże [My Travels] - Litwinowicz-Droździel, Małgorzata (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
This article refers to the memoirs of Ignacy Domeyko, a nineteenth-century geologist and emigrant who spent much of his life in Chile. Basing on a monographic reading of his Moje podróże [My Travels], it addresses three broader issues that extend beyond Domeyko’s individual experience and typify the period. The first is the standardisation of time, control over it, and planning as a form of ‘colonising’ the future. The second is the émigré condition with the attendant experience of limited agency and unpredictability, in contrast to the figure of the ‘modern man’ endowed with varied agency and command over time. The third is the perspective of geological time tied to Domeyko’s professional experiences of exploring Earth’s history and, thus, of measures of time extending beyond the human scale and control.
p. 113-133
Keywords: Domeyko, Ignacy (1802-1889); modernity; Great Emigration; history of geology; history of Polish science; science - Poland - history - 19th century; geology - history; Polish people - Europe - history - 19th century; time perception - history